Illuminative Ontology and the Construction of the Ideal Society in Ayatollah Khomeini’s Political Thought - Bogdana Todorova (UIN Sunan Gunung Djati Bandung, 2026)
This study examines the influence of Illuminative Philosophy (Hikmah al-Ishrāq) on the construction of the concept of the ideal society in Ayatollah Khomeini’s political thought. The research is important because most previous studies on Khomeini have emphasized revolutionary politics, constitutional structure, or ideological formulation, while giving less attention to the metaphysical foundations of political legitimacy in his thought. This study employs a qualitative library research approach using historical-intellectual inquiry and hermeneutic-conceptual analysis. Data were collected through systematic document analysis of Khomeini’s major political and mystical works, read alongside key texts from Suhrawardi, Mullā Ṣadrā, Plato, and al-Fārābī, as well as relevant secondary scholarship. The study finds that Khomeini’s concept of the ideal society constitutes a political articulation of an illuminative-ontological structure that emphasizes a hierarchy of existence and spiritual authority. Khomeini interprets Wilāyat al-Faqīh as a mediation between transcendent reality and social order, thereby grounding political legitimacy in ontological and epistemological foundations rather than merely normative-legal reasoning. The findings expand the understanding of the metaphysical foundations of modern Islamic political theory and demonstrate that metaphysics can function as a source of state legitimacy within modernity. The originality of this study lies in its integrative reading of Illuminative Philosophy, ‘irfan, and Khomeini’s theory of the state as a coherent epistemic paradigm.